ChemInform Abstract: Recent Advances in Porous Polyoxometalate‐Based Metal—Organic Framework Materials. Issue 34 (26th August 2014) - Du, Dong‐Ying; Qin, Jun‐Sheng; Li, Shun‐Li; Su, Zhong‐Min; Lan, Ya‐Qian
Abstract Review: classification, synthesis strategies, and applications, especially in the field of catalysis; 125 refs.